AUGMENTATION TECHNIQUES OF CONVECTIVE HEAT TRANSFER OF HEAT SINKS: A COMPREHENSIVE REVIEW - Khayoon Mohsen, Hiba; Hamza, Naseer (Journal of Engineering and Sustainable Development, 2023)
A heat sink is a heat exchanger that is commonly attached to an electronic device in order to remove excess heat. It cools circuit components by dissipating excess heat, thereby preventing overheating and premature component failure and enhancing component dependability and performance. The extruded geometries of the heat sink are either flat-plate fins or pin fins. Due to the development of micro-devices and nanotechnology over the past few decades, there has been a substantial emphasis on the miniaturization of electrical equipment. However, heat dissipation continues to be a significant challenge in improving the thermal performance of the heat sink. This article provides a thorough analysis of the techniques for optimizing the heat sinks designed hydrothermally. Therefore, the research that is currently accessible on passive and active methods of augmentation heat subtraction from heat sinks by altering either the solid or fluid domains is covered. This study aims to summarise the research efforts devoted to improving the thermal performance of heat sinks, as well as their limitations and proposed unresolved solutions. The current survey reports the significance of the orientation and shape of the fin besides the operating conditions regarding the type of flow and the boundary conditions. The maximum increment in Nusselt number obtained in the laminar flow over different orientations and shapes of fins was about two-thirds while in the case of turbulent flow was approximately double.